Co-digestion of swine excreta associated with increasing levels of crude glycerin - Previdelli Orrico Junior, Marco Antonio; Schwingel, Alice Watte [UNESP]; Centurion, Stanley Ribeiro; Amorim Orrico, Ana Carolina (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2016)
The objective of this research was to evaluate the performance of anaerobic co-digestion of swine excreta associated with increasing doses of crude glycerin and different hydraulic retention times (HRT). A completely randomized design was adopted in a 3 x 4 factorial arrangement composed of three HRT (10, 17, and 24 days) and four crude glycerin doses (0, 5, 10, and 15 g/100 g of total solids [TS]), with four replications per treatment. The assessed parameters were: biogas production potential, reductions of volatile solids (VS), chemical oxygen demand (COD), and most probable number of total and thermotolerant coliforms. The biogas production per added VS presented quadratic effect at 17 and 24 days of HRT, with ideal doses of 5.5 and 5.9 g of crude glycerin/100 g TS, respectively. There was no difference among glycerin doses at 10-day HRT for VS reductions; however, at HRT of 17 and 24 days, there were differences, with greater reduction of 61.1% for 5 g of crude glycerin/100 g TS at 24-day HRT. The COD reduction values showed an effect among retention times, in which the 24-day HRT provided the best results. Reductions in coliforms were greater than 99%, with no difference among treatments. Addition of 5 to 6 g of crude glycerin/100 g TS with a 24-day HRT is more effective in biogas production and reduction of VS, COD, and coliforms from co-digestion of swine excreta.
Keywords: biodiesel; biogas; manure; waste